Timescale analysis of a mathematical model of acetaminophen metabolism and toxicity. (7th December 2015) - Reddyhoff, Dennis; Ward, John; Williams, Dominic; Regan, Sophie; Webb, Steven
Abstract: Acetaminophen is a widespread and commonly used painkiller all over the world. However, it can cause liver damage when taken in large doses or at repeated chronic doses. Current models of acetaminophen metabolism are complex, and limited to numerical investigation though provide results that represent clinical investigation well. We derive a mathematical model based on mass action laws aimed at capturing the main dynamics of acetaminophen metabolism, in particular the contrast between normal and overdose cases, whilst remaining simple enough for detailed mathematical analysis that can identify key parameters and quantify their role in liver toxicity. We use singular perturbation analysis to separate the different timescales describing the sequence of events in acetaminophen metabolism, systematically identifying which parameters dominate during each of the successive stages. Using this approach we determined, in terms of the model parameters, the critical dose between safe and overdose cases, timescales for exhaustion and regeneration of important cofactors for acetaminophen metabolism and total toxin accumulation as a fraction of initial dose. Abstract : Graphical abstract: Abstract : Highlights: We have created a model, examining acetaminophen metabolism and related hepatotoxicity. We modeled multiple pathways associated with APAP metabolism. Using numerical, sensitivity and timescale analysis we have identified key parameters. Analysis highlights a critical acetaminophen dose in terms of the model parameters..